Monkeypox in human pregnancy: an overview - Sulaiman Muhammad Daneji, MBBS, FWACS; Aliyu Aminu, MBBS, FMCPath; Awwal Musa Borodo, MBBS, MSc, FWACP, FMCPath; Farouq Muhammad Dayyab, MBBS, MPH, FMCP (Elsevier, 2022)
Monkeypox is a viral zoonosis caused by the monkeypox virus, an enveloped, double-stranded DNA virus belonging to the Orthopoxvirus genus in the Poxviridae family. Monkeypox has become a disease of global public health significance. Pregnant women are unfortunately among the those at an increased risk for exposure to monkeypox because their immune system is altered during pregnancy. They may also be at risk for more severe disease or a worse outcome than others. During pregnancy or while breastfeeding when consideration is given for pre-exposure or postexposure vaccination, nonreplicating (Modivied Vaccinia Ankara - Bavarian Nordic) or minimally replicating (LC16, KM Biologics) vaccines are preferred. The ACAM2000 vaccine is contraindicated in pregnancy because it contains live virus particles that can cause fetal vaccinia and fetal death. There are no data to support the use of tecovirimat in pregnant women. However, no fetal adverse effects were noticed when tecovirimat was used in animal studies.